Identification of novel non-toxic and anti-angiogenic α-fluorinated chalcones as potent colchicine binding site inhibitors. (31st December 2022) - Sun, Moran; Yuan, Minghua; Kang, Yingying; Qin, Jinling; Zhang, Yixin; Duan, Yongtao; Wang, Longfei; Yao, Yongfang
Abstract: α-Fluorinated chalcones were prepared and evaluated for their cell growth inhibitory properties against six human cancer cell lines. The most potent chalcone 4c demonstrated excellent selective toxicity against cancer cells versus normal human cells, with IC50 values at nanomolar concentration ranges against 5 cancer cell lines. A further study revealed that 4c could bind to the colchicine site of tubulin, disrupt the cell microtubule networks, and effectively inhibit tubulin polymerisation. Cellular-based mechanism studies elucidated that 4c arrested MGC-803 cell cycle at G2/M phase. In addition, 4c dose-dependently caused Caspase-induced apoptosis of MGC-803 cells through mitochondrial dysfunction. Notably, compound 4c was found to inhibit the HUVECs tube formation, migration, and invasion in vitro . Furthermore, our data suggested that treatment with 4c significantly reduced MGC-803 cells metastasis and proliferation in vitro . Overall, this work showed that chalcone hybrid 4c is a potent inhibitor of tubulin assembly with prominent anti-angiogenesis and anti-cancer properties.